Voltaire's concept of international order - Perkins, M (Voltaire Foundation, 2017)
Preface Chapter I. Nations of the Earth Chapter II. European Politics Chapter III. International Law Chapter IV. Peace Projects of Saint-Pierre and Rousseau Chapter V. Enlightened Despots Chapter VI. Sources of War Chapter VII. Individual Right and Popular Sovereignty Chapter VIII. National Power and Foreign Policy Chapter IX. Concept of International Order Appendix I. Illustrative Texts Appendix II. Some Pertinent Books in Voltaire's Library Partial list of works consulted by the author Index of persons